Editor's Choice – The Impact of Centralisation and Endovascular Aneurysm Repair on Treatment of Ruptured Abdominal Aortic Aneurysms Based on International Registries. (August 2018) - Budtz-Lilly, Jacob; Björck, Martin; Venermo, Maarit; Debus, Sebastian; Behrendt, Christian-Alexander; Altreuther, Martin; Beiles, Barry; Szeberin, Zoltan; Eldrup, Nikolaj; Danielsson, Gudmundur; Thomson, Ian; Wigger, Pius; et al.
Abstract : Objectives: Current management of ruptured abdominal aortic aneurysms (RAAA) varies among centres and countries, particularly in the degree of implementation of endovascular aneurysm repair (EVAR) and levels of vascular surgery centralisation. This study assesses these variations and the impact they have on outcomes. Materials and methods: RAAA repairs from vascular surgical registries in 11 countries, 2010–2013, were investigated. Data were analysed overall, per country, per treatment modality (EVAR or open aortic repair [OAR]), centre volume (quintiles IV), and whether centres were predominantly EVAR (≥50% of RAAA performed with EVAR [EVAR(p)]) or predominantly OAR [OAR(p)]. Primary outcome was peri-operative mortality. Data are presented as either mean values or percentages with 95% CI within parentheses, and compared with chi-square tests, as well as with adjusted OR. Results: There were 9273 patients included. Mean age was 74.7 (74.5–74.9) years, and 82.7% of patients were men (81.9–83.6). Mean AAA diameter at rupture was 7.6 cm (7.5–7.6). Of these aneurysms, 10.7% (10.0–11.4) were less than 5.5 cm. EVAR was performed in 23.1% (22.3–24.0). There were 6817 procedures performed in OAR(p) centres and 1217 performed in EVAR(p) centres. Overall peri-operative mortality was 28.8% (27.9–29.8). Peri-operative mortality for OAR was 32.1% (31.0–33.2) and for EVAR 17.9% (16.3–19.6), p  < .001, and the adjusted OR was 0.38 (0.31–0.47), p  < .001. The peri-operative mortality was 23.0% in EVAR(p) centres (20.6–25.4), 29.7% in OAR(p) centres (28.6–30.8), p  < .001; adjusted OR = 0.60 (0.46–0.78), p  < .001. Peri-operative mortality was lower in the highest volume centres (QI > 22 repairs per year), 23.3% (21.2–25.4) than in QII-V, 30.0% (28.9–31.1), p  < .001. Peri-operative mortality after OAR was lower in high volume centres compared with the other centres, 25.3% (23.0–27.6) and 34.0% (32.7–35.4), respectively, p  < .001. There was no significant difference in peri-operative mortality after EVAR between centres based on volume. Conclusions: Peri-operative mortality is lower in centres with a primary EVAR approach or with high case volume. Most repairs, however, are still performed in low volume centres and in centres with a primary OAR strategy. Reorganisation of acute vascular surgical services may improve outcomes of RAAA repair.